2011
DOI: 10.1073/pnas.1101553108
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wingless ( Wnt ) signaling in pituitary progenitor/stem cells gives rise to pituitary tumors in mice and humans

Abstract: Wingless (Wnt)/β-catenin signaling plays an essential role during normal development, is a critical regulator of stem cells, and has been associated with cancer in many tissues. Here we demonstrate that genetic expression of a degradation-resistant mutant form of β-catenin in early Rathke's pouch (RP) progenitors leads to pituitary hyperplasia and severe disruption of the pituitary-specific transcription factor 1-lineage differentiation resulting in extreme growth retardation and hypopituitarism. Mutant mice m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
294
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 260 publications
(310 citation statements)
references
References 41 publications
15
294
0
1
Order By: Relevance
“…Expression of oncogenic β‐catenin in the developing pituitary in Hesx1 Cre/+ ;Ctnnb1 lox(ex3)/+ mice results in tumors resembling human ACP at the histological and molecular levels 11. Despite activation of β‐catenin in all pituitary cells in this model, nuclear accumulation is only observed in small clusters of cells, analogous to human clusters.…”
Section: Introductionmentioning
confidence: 79%
“…Expression of oncogenic β‐catenin in the developing pituitary in Hesx1 Cre/+ ;Ctnnb1 lox(ex3)/+ mice results in tumors resembling human ACP at the histological and molecular levels 11. Despite activation of β‐catenin in all pituitary cells in this model, nuclear accumulation is only observed in small clusters of cells, analogous to human clusters.…”
Section: Introductionmentioning
confidence: 79%
“…These cells could therefore act as signalling centres, likely changing the microenvironment and facilitating tumorigenesis (Andoniadou et al 2012(Andoniadou et al , 2013). An observation that was indicative of the potential of these cluster cells was that actively proliferating cells, as marked by immunofluorescence of Ki67, were readily detected in close proximity to the cell clusters in both mouse and human ACP (Gaston-Massuet et al 2011). Several of the identified cytokines and growth factors have been shown to play a role in normal pituitary physiology as well as in pituitary adenomas (Arzt et al 1999(Arzt et al , 2009Graciarena et al 2004).…”
Section: Stem Cells and Pituitary Tumoursmentioning
confidence: 96%
“…We expressed this mutation embryonically throughout the developing pituitary primodium, from the early specification of Rathke's pouch using the Hesx1-Cre driver. Hesx1 Cre/+ ; Ctnnb1 lox(ex3)/+ animals develop tumours very similar to human ACP and contain the hallmark β-catenin-accumulating cell clusters that activate the WNT/β-catenin pathway (Gaston-Massuet et al 2011). We assessed the mouse tumours for the presence of cells reminiscent of CSCs, which have self-renewal and differentiation properties in vitro, and found an increase of clonogenic cells, up to three times the number compared to normal pituitaries (Gaston-Massuet et al 2011).…”
Section: Stem Cells and Pituitary Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hesx1 Cre/+ (49), Tcf7l1 flox/flox (44), and Tcf7l1 ΔN/ΔN (33) have been previously described. We have previously shown that the Hesx1-Cre mouse line drives efficient recombination of loxP-flanked DNA in RP progenitors from 9.5 dpc (49,50). Hesx1 Cre/+ ;R26 loxP-YFP/+ 18.5 dpc embryos display widespread yellow fluorescent protein (YFP) expression in the vast majority of cells of the anterior pituitary, suggesting that the Hesx1-expressing RP progenitors give rise to all hormone-producing cells (Hesx1-cell lineage).…”
Section: Methodsmentioning
confidence: 99%